Prevalence of Early Initiation of Breastfeeding Among Postpartum Mothers in Baregbeg Primary Health Center - Kurniati Devi Purnamasari; Widya Maya Ningrum; Adhelia Dwi Lestari (Journal of Midwifery and Public Health, 2025)
Background: Early Initiation of Breastfeeding (EIBF) within the first hour after birth is a critical intervention to improve exclusive breastfeeding rates and reduce neonatal mortality. However, its implementation in primary healthcare settings remains suboptimal, indicating a gap between policy and practice. Objective: This study aimed to describe the implementation of Early Initiation of Breastfeeding among newborns at Baregbeg Public Health Center. Methods: A descriptive quantitative study with a cross-sectional approach was conducted. The sample included 22 postpartum mothers (0–40 days) selected using total sampling. Data were collected using observation sheets and analyzed through univariate analysis. Results: The findings showed that 72.7% of mothers implemented EIBF, while 27.3% did not, indicating that although the majority practiced EIBF, a considerable proportion still missed early breastfeeding initiation. Conclusion: The implementation of EIBF at Baregbeg Public Health Center is generally adequate but not yet optimal. Strengthening maternal education and enhancing health worker support are essential to improve EIBF coverage and ensure consistent practice.